1989
DOI: 10.1007/bf00048305
|View full text |Cite
|
Sign up to set email alerts
|

Energy transfer to low energy chlorophyll species prior to trapping by P700 and subsequent electron transfer

Abstract: It is found that the two singlet state lifetimes observed in medium sized isolated Photosystem One reaction centres belong to two distinct sets of particles. The nanosecond lifetime is due to PS1 particles in which P700 does not trap excitation energy, and the excitation energy is homogeneously distributed within the antennae of these particles. The spectral features of the picosecond component show that excitation energy in the antenna has become largely concentrated in one or more low energy (red) chlorophyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
1

Year Published

1993
1993
2007
2007

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 21 publications
6
35
1
Order By: Relevance
“…The difference spectrum of the transient spectra between the P740‐prereduced and ‐preoxidized conditions, which we designate red‐ox transient spectrum, should manifest the Chls involved in the electron transfer, as done in the past studies on cyanobacterial/plant PS I [13–16]. The red‐ox transient spectra detected with the strong excitation pulses (80 nJ/pulse) are shown in Fig.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…The difference spectrum of the transient spectra between the P740‐prereduced and ‐preoxidized conditions, which we designate red‐ox transient spectrum, should manifest the Chls involved in the electron transfer, as done in the past studies on cyanobacterial/plant PS I [13–16]. The red‐ox transient spectra detected with the strong excitation pulses (80 nJ/pulse) are shown in Fig.…”
Section: Resultsmentioning
confidence: 92%
“…The (P700‐prereduced‐minus‐preoxidized) transient spectra showed only a growth of the P700 + /P700 difference spectrum without substantial signal of A 0 − /A 0 at 685–690 nm (unpublished data). This is presumably due to the fast 13–30 ps reoxidation of A 0 − that is comparable to or even faster than the trapping of excitation energy (22–69 ps) in PS I with large antenna sizes [13–16,26].…”
Section: Discussionmentioning
confidence: 99%
“…We regard that the ≈1-ps equilibration process achieves full equilibration of the excited states for simplicity in the following discussion. (47) This probability is different from that in ref 11, where P P700 e was given by the product of the number of Chl molecules forming P700 (2) and the Boltzmann distribution probability. However, the factor of 2 is not necessary if P700* is one excited state delocalized over two chlorophyll molecules.…”
Section: Appendixmentioning
confidence: 81%
“…The spectral composition of the PSI core antenna Chls emerging from spectroscopic studies comprises several spectral forms of bulk Chls with Q Y bands peaking at between~673 (the most abundant) and~698 nm (Melkozernov et al 2000;Gobets et al 1994) and a speciesdependent number of red Chls absorbing at >700 nm. Several antenna Chls were shown to form dimers or trimers Byrdin et al 2002;Damjanović et al 2002;Sener et al 2002), and were proposed to be the red Chls (Klug et al 1989;Melkozernov et al 2000a, b). No red Chls, absorbing at >700 nm, were observed in C. reinhardtii PSI core preparations (Gibasiewicz et al 2001(Gibasiewicz et al , 2002.…”
Section: Introductionmentioning
confidence: 97%
“…On the basis of femtosecond transient absorption measurements, it was suggested that within a few picoseconds after excitation of PSI core, energy is equilibrated over a small subset of relatively low-energy antenna Chls located close to the RC (Gibasiewicz et al 2001(Gibasiewicz et al , 2002; see also Klug et al 1989 andMelkozernov et al 2001). The maximum photobleaching/stimulated emission (PB/SE) signal of this pool is at~683-685 nm (Gibasiewicz et al 2001(Gibasiewicz et al , 2002Savikhin et al 2000;Melkozernov et al 2000a;Gobets et al 2003) and is independent of excitation wavelength (Gibasiewicz et al 2001).…”
Section: Introductionmentioning
confidence: 98%